2019
DOI: 10.1158/1078-0432.ccr-18-1589
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic Therapy with Panobinostat Combined with Bicalutamide Rechallenge in Castration-Resistant Prostate Cancer

Abstract: This study assesses the action of panobinostat, a histone deacetylase inhibitor (HDACI), in restoring sensitivity to bicalutamide in a castration-resistant prostate cancer (CRPC) model and the efficacy and safety of the panobinostat/bicalutamide combination in CRPC patients resistant to second-line antiandrogen therapy (2LAARx). The CWR22PC xenograft and isogenic cell line were tested for drug interactions on tumor cell growth and on the androgen receptor (AR), AR-splice variant7, and AR targets. A phase I tri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…Preclinical shreds of evidence suggested that resistance to bicalutamide 48 treatment could be overcome through the simultaneous administration of panobinostat 6 , synergistically inducing apoptosis and growth arrest better than those obtained with panobinostat 6 alone, in both isogenic cell line and xenograft model of castration‐resistant prostate cancer (CRPC) . In 2018, a phase I/II clinical trial (NCT00878436) conducted by Ferrari et al highlighted the capability of panobinostat 6 to restore sensitivity to bicalutamide 48 (Combination O, Figure ) in a CRPC cancer model, as well as the safety and efficacy of its combination with bicalutamide 48 in CRPC second‐line androgen resistant condition. The phase I trial was characterized by a 3 × 3 panobinostat 6 dose escalation design and the phase II trial involved randomized 55 patients treated with 20 or 40 mg of panobinostat 6 tri‐weekly for 2 weeks in association with bicalutamide 48 50 mg/d in 3‐week cycle.…”
Section: The Mmt Approachmentioning
confidence: 99%
“…Preclinical shreds of evidence suggested that resistance to bicalutamide 48 treatment could be overcome through the simultaneous administration of panobinostat 6 , synergistically inducing apoptosis and growth arrest better than those obtained with panobinostat 6 alone, in both isogenic cell line and xenograft model of castration‐resistant prostate cancer (CRPC) . In 2018, a phase I/II clinical trial (NCT00878436) conducted by Ferrari et al highlighted the capability of panobinostat 6 to restore sensitivity to bicalutamide 48 (Combination O, Figure ) in a CRPC cancer model, as well as the safety and efficacy of its combination with bicalutamide 48 in CRPC second‐line androgen resistant condition. The phase I trial was characterized by a 3 × 3 panobinostat 6 dose escalation design and the phase II trial involved randomized 55 patients treated with 20 or 40 mg of panobinostat 6 tri‐weekly for 2 weeks in association with bicalutamide 48 50 mg/d in 3‐week cycle.…”
Section: The Mmt Approachmentioning
confidence: 99%
“…The non-selective histone deacetylase inhibitor panobinostat (Figure 2D) and the suberolylanilide hydroxaminic acid vorinostat (Figure 2D) have been evaluated in association with docetaxel in patients with advanced solid malignancies (vorinostat) and metastatic CRPC (panobinostat) [66,67,68,69]. Unfortunately, the combination of vorinostat and docetaxel resulted in excessive dose-limiting toxicity [66] while a better safety profile has been observed with the combination of panobinostat and docetaxel [67].…”
Section: How To Overcome Resistance To Ar Inhibitionmentioning
confidence: 99%
“…More recently, a phase II study evaluating intravenous panobinostat failed to show significant clinical activity of this drug [68]. Despite these results, a study carried out by Ferrari et al on xenograft and isogenic cell line demonstrated that the addiction of panobinostat to bicalutamide prolonged tumor sensitivity to bicalutamide, suggesting an adoption of this drug in combination with androgen deprivation therapy [69]. Of note, the combination between an acetylase inhibitor (CCS1477) and abiraterone is under evaluation in a phase I/II trial (NCT03568656).…”
Section: How To Overcome Resistance To Ar Inhibitionmentioning
confidence: 99%
“…Although the molecular details of how these opposing enzymes affect the AR transcriptional processes is incompletely understood, a consistent paradoxical finding in CRPC models is that HDACs, which are classically a key component of the repressor complex, are required for AR mRNA transcription and protein stability and for transcriptional activation of AR target genes [6]. Accordingly, pan HDAC inhibitors (HDACIs), such as Panobinostat, uniformly reduce AR mRNA levels, including ARSv7 in CRPC models [7]. Consequently, AR protein synthesis and levels are also diminished by HDACIs, although there are conflicting data about the contribution of cytoplasmic AR protein degradation via HDACI-induced acetylation of the transporter protein HSP90 [6].…”
mentioning
confidence: 99%
“…We demonstrated in preclinical experiments with CRPC culture/xenograft models that overexpress AR and ARSv7 that there is synergistic inhibition of cell growth by Panobinostat in combination with the antiandrogen bicalutamide in cells resistant to bicalutamide [7, 8]. Notably, an approximately 2-fold higher concentration of Panobinostat in the combination was required to further produce apoptosis [8].…”
mentioning
confidence: 99%